EFIKASI ANTIOKSIDAN AKAR TERUNG PIPIT (Solanum torvum) TERHADAP KERUSAKAN HATI DENGAN INDUKSI CCL4 PADA Rattus norvegicus: Efikasi Antioksidan Akar Terung Pipit (Solanum torvum) terhadap Kerusakan Hati dengan Induksi CCL4 pada Rattus norvegicus - Rivan Virlando Suryadinata; Dwi Martha Nur Aditya; Ryu Okiku Christina Gunawan; Mudita Lestari Utami; Bambang Wirjatmadi (Universitas Airlangga, 2022)
Background: Liver disease is still a health problem in the world. In Indonesia, liver disease is dominated by liver cirrhosis. One of the causes of liver damage is an increase in the number of free radicals in the body. This will result in damage and death of liver cells and cause fibrotic tissue. A decrease in the number of liver cells will result in impaired overall liver function. Giving antioxidants can reduce free radicals that enter the body. One of the plants that contain antioxidants is the terung pipit (Solanum torvum). Objectives: This study aims to determine the antioxidant efficacy of terung pipit root (Solanum torvum) against liver damage by CCL4 induction in Rattus norvegicus. Methods: This research is experimental using a Randomized Controlled Trial (RCT) design. The research process was carried out for 11 days by dividing the experimental animals into 6 groups with 5 individuals in each group. Each treatment group will be induced with CCL4 for 5 days and followed by 7 days of administration of terung pipit root (Solanum torvum) with different doses (0.5; 1.0; 1.5 mg/grBB/day). The parameters used are the levels of SGOT-SGPT and bilirubin in the blood. Results: The results showed a decrease in the levels of SGOT-SGPT and bilirubin in the blood in the group given the terung pipit root (p≤0,05). Increasing the dose of terung pipit root administration further decreased the research parameters, although it did not reach the value of the negative control group. Conclusions: The antioxidant content in terung pipit root (Solanum torvum) can decrease in SGOT-SGPT and bilirubin levels in the blood due to liver damage in experimental animals induced by CCL4.